1998 - 1999 Catalog - Office of the Provost (Southwest Baptist University, 1998)
This catalog is designed primarily for the faculty and students of Southwest Baptist University and for students planning to enter SBU. Its pages contain the objectives of the University; outlines of the programs of study; admission and graduation requirements; and information regarding costs, living conditions, scholarships, counseling services and student life. This catalog is a description and official register of Southwest Baptist University and is a working agreement between a student and the University. A student is responsible for being fully aware of and fulfilling all regulations and conditions contained or referred to herein or as such regulations and conditions may hereafter be amended by the University if and when it deems necessary. As conditions of admission, the University reserves the right and power to discipline or dismiss any student who fails to comply with said regulations and conditions, and each student agrees that the University shall have such right and power of discipline or dismissal.